Function of Small Peptides During Male-Female Crosstalk in Plants - Zhang, Jinghua; Yue, Ling; Wu, Xiaolin; Liu, Hui; Wang, Wei (Frontiers in Plant Science, 2021)
Plant peptides secreted as signal molecular to trigger cell-to-cell signaling are indispensable for plant growth and development. Successful sexual reproduction in plants requires extensive communication between male and female gametophytes, their gametes, and with the surrounding sporophytic tissues. In the past decade, it has been well documented that small peptides participate in many important reproductive processes such as self-incompatibility, pollen tube growth, pollen tube guidance, and gamete interaction. Here, we provide a comprehensive overview of the peptides regulating the processes of male-female crosstalk in plant, aiming at systematizing the knowledge on the sexual reproduction and signaling of plant peptides in future.